Community policing on American Indian reservations: a preliminary investigation. Issue 5 (10th October 2022) - Crepelle, Adam; Fegley, Tate; Murtazashvili, Ilia; Murtazashvili, Jennifer Brick
Abstract: In the 1970s, Elinor Ostrom and her colleagues found that neighborhood policing works better than metropolitan policing. Though Ostrom articulated design principles for self-governance, the early studies of neighborhood policing did not. In this paper, we articulate the design principles for self-governing policing, which we term Ostrom-Compliant Policing. We then apply this framework to an understudied case: policing on American Indian reservations. Policing in Indian country generally falls into one of three categories – federal policing (by the Bureau of Indian Affairs and Federal Bureau of Investigation), state policing (by municipal and state police departments), and tribal policing (by tribal police departments) – that vary in the degree of centralization. Our main contribution is to show that tribal policing as it is practiced in the United States, which claims to be self-governing, is not Ostrom-Compliant. Thus, our approach offers insight into why high crime remains an ongoing challenge in much of Indian country even when tribes have primary control over policing outcomes. This does not mean centralization is better, or that self-governance of policing does not work. Rather, our research suggests that a greater tribal autonomy over-policing and meta-political changes to federal rules governing criminal jurisdictions is necessary to implement Ostromian policing.